HARMONISASI HUKUM PERIKANAN UNTUK KESEJAHTERAAN KELAUTAN INDONESIA - Emiel Salim Siregar; Celly Naomi Sarah Br Napitupulu; Lica Adilla; Nurul Akmal; Muhammad Idham (Yustitia, 2025)
The rapid growth of the fisheries industry in Indonesia highlights the urgent need to formulate and implement legal policies that are in line with sustainability principles. This abstract discusses efforts to "Harmonize Fisheries Law for Indonesia's Marine Welfare," with a focus on achieving long-term goals involving economic, ecological, and social aspects. The paradigm shift from overexploitation to sustainable management requires integration and consistency between applicable legal regulations. This research highlights the importance of addressing interregulatory conflicts, increasing supervision, and implementing effective sanctions to support sustainability principles. In addition, harmonization of fisheries regulations at various levels of government, from local to national levels, is essential to ensure good coordination in policy implementation. By detailing the positive impact of the harmonization of fisheries laws, the term